Freedom of thought - "Bury, J.B." (New York, 2007)
This book looks over the greatest battle of human history, the fight between rationalism and the oppressive regimes society constantly imposes on free thinkers. From ancient Greece through to the early 1900s. The author thought that rationalism had won a victory, but the modern listener will feel a creeping dread as parallels with movements in today's society are revealed.
Keywords: Thoughts & thinking-History